Best Practices and Innovations in Modern Financial Statement Audits - Ikhtiari, Kirana (Advances in Managerial Auditing Research, 2023)
Purpose: This research explores best practices and innovations in modern financial statement auditing, considering the dynamic evolution of audit methodologies and the regulatory landscape. This research focuses on understanding the latest trends, challenges, and emerging best practices in financial statement auditing. Research Design and Methodology: A qualitative approach was used by conducting a comprehensive literature review to synthesize perspectives, theories, and findings from scholarly articles, books, reports, and other relevant sources. The research analyzed the literature to identify emerging trends and innovations in modern audit practice. Findings and Discussion: The findings reveal a significant transformation in audit methodologies driven by technological advancements and regulatory pressures. Advanced technologies such as data analytics, artificial intelligence (AI), and blockchain have revolutionized audit procedures, improving audit effectiveness, efficiency, and transparency. Regulatory compliance and corporate governance are at the top of the mind, with auditors playing a critical role in promoting transparency, accountability, and trust in financial reporting. Implications: This research contributes to the development of modern financial statement audit knowledge and practice, emphasizing the role of auditors in dealing with complex regulatory environments and adopting technological innovations to meet evolving stakeholder expectations.